Motorola Xoom companion - Ballew, Joli (Wiley Pub., 2011)
An easy-to-follow guide that helps you get the most out of your Xoom device Motorola Xoom is one of the hottest new tablets but the owner's manual only goes so far to cover features and functions. This full-color guide is packed with useful tips, invaluable advice, and easy-to-follow shortcuts that help you quickly get acquainted with the Motorola Xoom OS. You'll explore tasks such as working with e-mail, messaging, browsing, utilizing the calendar, making appointments, enjoying and sharing photos and music, using maps, referencing contacts, adjusting the settings, working with security, check.